Development of a Lateral Flow Strip-Based Recombinase-Aided Amplification for Active Chlamydia psittaci Infection - Jiao, Jun; Qi, Yong; He, Peisheng; Wan, Weiqiang; OuYang, Xuan; Yu, Yonghui; Wen, Bohai; Xiong, Xiaolu (Frontiers in Microbiology, 2022)
Chlamydia psittaci is the causative agent of psittacosis, a worldwide zoonotic disease. A rapid, specific, and sensitive diagnostic assay would be benefit for C. psittaci infection control. In this study, an assay combining recombinase-aided amplification and a lateral flow strip (RAA-LF) for the detection of active C. psittaci infection was developed. The RAA-LF assay targeted the CPSIT_RS02830 gene of C. psittaci and could be accomplished in 15 min at a single temperature (39°C). The analytical sensitivity of the assay was as low as 1 × 100 copies/μl and no cross-reaction with some other intracellular pathogens was observed. Moreover, all feces samples from mice infected with C. psittaci at day-1 post-infection were positive in the RAA-LF assay. In conclusion, the RAA-LF assay provides a convenient, rapid, specific and sensitive method for detection of active C. psittaci infection and it is also suitable for C. psittaci detection in field.